Privatising Peacekeeping (Czech Journal of International Relations, 2006)
This article offers a comprehensive analysis of the perils and benefits of peacekeeping privatisation by approaching two key questions. Firstly, can private military companies (PMCs) take on peacekeeping functions consistent with the UN Charter's primary objective "to save future generations from the scourge of war"? And secondly, is peacekeeping privatisation really an option for bridging the UN's peacekeeping capabilities-expectations gap? PMCs' past performances here offer no clear-cut answers for the first question. Critics have doubted their cost-effectiveness, accountability and legitimacy, while proponents have argued their cost-effectiveness, feasibility and professionalism over their UN and/or regional counterparts. On the second question, PMCs posses many capabilities necessary for peacekeeping operations that the UN often lacks. Yet the question remains how far privatisation should extend, with the danger of it going too far too fast, causing PMC peacekeeping to become a substitute for, rather than an enhancement of, UN action.
Keywords: Peacekeeping; private military companies; United Nations; privatisation; outsourcing